Interleukin-2/Anti-Interleukin-2 Immune Complex Expands Regulatory T Cells and Reduces Angiotensin II-Induced Aortic Stiffening. (2nd September 2014) - Majeed, Beenish; Tawinwung, Supannikar; Eberson, Lance S.; Secomb, Timothy W.; Larmonier, Nicolas; Larson, Douglas F.
Abstract : Adaptive immune function is implicated in the pathogenesis of vascular disease. Inhibition of T-lymphocyte function has been shown to reduce hypertension, target-organ damage, and vascular stiffness. To study the role of immune inhibitory cells, CD4 + CD25 + Foxp3 + regulatory T cells (Tregs), on vascular stiffness, we stimulated the proliferation of Treg lymphocytes in vivo using a novel cytokine immune complex of Interleukin-2 (IL-2) and anti-IL-2 monoclonal antibody clone JES6-1 (mAb CD25 ). Three-month-old male C57BL/6J mice were treated with IL-2/mAb CD25 concomitantly with continuous infusion of angiotensin type 1 receptor agonist, [Val 5 ]angiotensin II. Our results indicate that the IL-2/mAb CD25 complex effectively induced Treg phenotype expansion by 5-fold in the spleens with minimal effects on total CD4 + and CD8 + T-lymphocyte numbers. The IL-2/mAb CD25 complex inhibited angiotensin II-mediated aortic collagen remodeling and the resulting stiffening, analyzed with in vivo pulse wave velocity and effective Young's modulus. Furthermore, the IL-2/mAb CD25 complex suppressed angiotensin II-mediated Th17 responses in the lymphoid organs and reduced gene expression of IL-17 as well as T cell and macrophage infiltrates in the aortic tissue. This study provides data that support the protective roles of Tregs in vascular stiffening and highlights the use of the IL-2/mAb CD25 complex as a new potential therapy in angiotensin II-related vascular diseases.